Regulating flexible work - McCann, Deirdre (Oxford University Press, 2008)
Analyzing in detail recent United Kingdom legislative reforms and the wider context of the EU and International Labor Organization, this book shows how, although flexible working arrangements are now more strongly protected, they are not fully integrated into UK labor law